Men pause and women talk too much: Power and gender negotiations in eliciting data during semi-structured interviews - DOHA ABUALSAUD (Journal of Advanced Research in Social Sciences and Humanities, 2019)
Aim: Rather than solely analyzing interview data, this interpretive study considers how the interview was conducted. The study’s overarching objective is to learn about graduate students’ perspectives and sentiments during their academic journey.Method: The phenomenological method was chosen for this investigation so that researchers could better comprehend the participants’ first-hand accounts of the phenomenon under study. Three current MSc students at the University of Exeter were interviewed; two were male, and one was female. All three interviews were semi-structured.Findings: It was clear from the data that the power dynamic during the interview was more pronounced between the two men than it was between the woman. Power dynamics between the interviewer and the interviewees surfaced at various points.Implications/Novel Contribution: This assignment in Interpretive Methodology lays the groundwork for future researchers interested in pursuing similar projects. It taught me things about research that will be useful in the future. A researcher’s understanding of what is expected of them and how to handle sticky situations during interviews can be bolstered by reflecting on their own semi-structured interviews.